Impact of a Single Spoiler on Scouring Depth Status Beneath a River Crossing Inclined Pipeline - Abbasi, S.; Masoomi, M.; Arjmandi, S. A. (Engineering, Technology & Applied Science Research, 2018)
Deep river crossing pipelines utilized to carry fluids are often placed upon the sand bed. Placement of pipe on the non-smooth bed would result in the production of some local gaps beneath the pipe. Asymmetric scouring is one of the main reasons for pipe underwater failures which are significant in pipeline management. So, in designing pipelines, knowing the interaction between pipelines and bed, and predicting the scour depth with respect to the pipe distance from the bed is significant to ensure that the pipe will finally deposit on the bed. Numerical models have been developed for predicting the balance depth of scouring beneath the pipelines. In this paper, the impact of pipe orientation on maximum scour depth beneath the pipelines is investigated. To do this, a pipe is modeled with various angles with the flow. To manage the local scouring, some spoilers are placed and modeled upon some pipes too. Also, in order to know the effects of placement of a pipe at various distances from the bed, the impact of placement of each pipe at a distance of 0.2D, 0.4D and 0.6D is investigated as well. To model the pipe with and without a spoiler, the finite element model Flow-3D is utilized and the results show good accordance with previous experimental studies and proof the current model’s precision in predicting the scour depth. Results show that in the placement of the pipe in angles not investigated before and also with the installing of a spoiler, the scour process has a reverse ratio with the distance which would result in full deposition of the pipe on the bed. The least scour depth belongs to the condition in which the pipe has a 130° angle with the side wall.